Biological Monitoring by Serum Choline Esterase In Different Occupational Groups Exposed to Pesticides (Journal of Chittagong Medical College Teachers' Association, 2019)
Background: Pesticide are used extensively in agriculture to enhance food production by eradicating unwanted insects. Pesticide can cause harm to human, animals, or the environment. The aim of this study to evaluate the biochemical changes in human of different occupational groups exposed to pesticide. Material and methods: The cross sectional comparative study was conducted in the department of biochemistry Chattogram Medical College, from January 2012 to December 2012. Total 100 subjects who fulfilled the enrollment criteria were included in this study. Among them 60, who were exposed to pesticides were included in group A or case or test subject and 40 who were not exposed to pesticides were included in group B or control. The occupational groups exposed to pesticide were randomly selected on the basis of their active involvement at least 5 years in preparation, storage and spraying of the pesticides. Results : The present study showed that serum Cholinesterase(ChE) was significantly lower in cases than that of control with p=